The Later Years: Women Instructors at the Winnipeg School of Art in the 1940s - Baker, Marilyn (Atlantis)

(untitled) (Mount Saint Vincent University, 2006)
Women were employed as art teachers at the Winnipeg School of Art in Winnipeg, Manitoba, in unusual numbers from 1940 to 1950. Beneficiaries of a proper art education, they "kept the home fires burning." When the men came back they were let go in what was seen as a return to normalcy.